Highland barley grain and soil surveys reveal the widespread deficiency of dietary selenium intake of Tibetan adults living along Yalung Zangpo River - Chenni Zhou; Chenni Zhou; Ran Xiao; Mo Li; Qi Wang; Wenfeng Cong; Fusuo Zhang (Frontiers in Sustainable Food Systems, 2022)
ObjectiveIn order to assess selenium (Se) flux through the soil-plant-human chain in Tibet plateau and explore the reason why local Tibetan adult residents from large scale agricultural production areas in Tibet lacked daily Se intake.MethodsA total of 210 intact highland barley plants and their corresponding cultivated topsoil samples were collected in fields of 14 agricultural counties along Yalung Zangpo River and quantitative dietary data were collected from a cross-sectional survey using a cultural-specific food frequency questionnaire that contained all local Tibetan foods in 2020.ResultsThe mean value of The estimated daily Se dietary intake by each participant was 17.1 ± 1.9 μg/day/adult, the Se concentration in topsoil and highland barley grain were 0.128 ± 0.015 mg/kg and 0.017 ± 0.003 mg/kg, respectively. Although highland barley was the first contributor of dietary Se in local adult residents (34.2%), the dietary Se intake provided by highland barley only about 10% of the EAR value (50 μg/day/adult) currently. A significantly positive relationship was determined between soil total Se content (STSe), available Se content (SASe) and highland barley grain Se content (GSe). The amount of Se in food system depends on a number of soil properties (TOC, pH, clay content, Fe/Mn/Al oxides), climate variables (MAP, MAT) and terrain factor (altitude).ConclusionTo sum up, it can be inferred that the insufficient dietary Se intake of Tibetan adult population living along Yalung Zangbo River is mainly caused by the low Se content in highland barley grain, which was result from the low Se content in cultivated soil. In order to enable adult participants in the present study to achieve recommended dietary Se-intake levels, agronomic fortification with selenised fertilizers applied to highland barley could be a great solution. It is necessary to combine the influencing factors, and comprehensively consider the spatial variation of local soil properties, climatic and topographic conditions, and planting systems.